Advanced visual sensing and control in CMT-based WAAM processes - Yu, Rui; Li, Wenhang; Wu, Mingfang; Wang, Jianxin; Han, Qinglin; Wang, Jiayou; Bing, Siyu (Frontiers in Materials, 2025)
Wire Arc Additive Manufacturing (WAAM) can flexibly produce high-performance parts that meet the requirements of deep-sea environments, but it has problems with insufficient molding accuracy and surface smoothness, which require improved precision and quality. To address these challenges, this paper establishes a WAAM experimental system based on Cold Metal Transfer (CMT) technology. First, the influence of process parameters on multi-layer single-channel forming was studied. Second, a structured light visual sensing system based on a high-speed camera was developed. Finally, a method for controlling the camera’s triggering mode at low voltage was designed, effectively eliminating arc interference. The experiment extracted and preprocessed the laser stripe ROI (Region of Interest), extracted geometric size information of the weld seam, and then performed median filtering to extract the centerline and feature points. By constructing a CMT-based WAAM monitoring system, high reliability and quality control of the manufacturing process and weld formation have been achieved.